Stable accumulation of Aspergillus niger phytase in transgenic tobacco leaves. - Verwoerd, T C (1995)
Phytase from Aspergillus niger increases the availability of phosphorus from feed for monogastric animals by releasing phosphate from the substrate phytic acid. A phytase cDNA was constitutively expressed in transgenic tobacco (Nicotiana tabacum) plants. Secretion of the protein to the extracellular fluid was established by use of the signal sequence from the tobacco pathogen-related protein S. The specific phytase activity in isolated extracellular fluid was found to be approximately 90-fold higher than in total leaf extract, showing that the enzyme was secreted. This was confirmed by use of immunolocalization. Despite differences in glycosylation, specific activities of tobacco and Aspergillus phytase were identical. Phytase was found to be biologically active and to accumulate in leaves up to 14.4% of total soluble protein during plant maturation. Comparison of phytase accumulation and relative mRNA levels showed that phytase stably accumulated in transgenic leaves during plant growth.